2016
DOI: 10.1080/14658011.2016.1183335
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and mechanism of anionic waterborne polyurethane dispersion for chemical sand stabilisation

Abstract: Chemical sand stabilisation (CSS) shows potential to collaborate with vegetation for desert restoration. Among the materials used in CSS, polyurethane (PU) is one of excellent properties but restricted by the limited forms used for CSS. This paper presents an anionic waterborne PU dispersion (PUD), a dispersion form of PU, for CSS. Its composition, particle size distribution (PSD) and zeta potential were characterised by Fourier transform infrared spectroscopy and laser particle size analyser. Results of its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…As shown in Figure 4, it is the consolidation layer formed after the application of a new sand fixing agent called ADNB(The aqua-dispersing-nano-binder) developed by our team [82]. Thus, the sand fixing agent can fix sand, resist wind erosion, and retain water [83][84][85][86].…”
Section: Chemical Sand Fixation Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, it is the consolidation layer formed after the application of a new sand fixing agent called ADNB(The aqua-dispersing-nano-binder) developed by our team [82]. Thus, the sand fixing agent can fix sand, resist wind erosion, and retain water [83][84][85][86].…”
Section: Chemical Sand Fixation Measuresmentioning
confidence: 99%
“…As shown in Figure 4, it is the consolidation layer formed after the application of a new sand fixing agent called ADNB(The aqua-dispersing-nano-binder) developed by our team [82]. Thus, the sand fixing agent can fix sand, resist wind erosion, and retain water [83][84][85][86]. During this process, the silt and clay particles are bonded to form soil agglomerates of different sizes, and their content does not change significantly [87][88][89][90].…”
Section: Chemical Sand Fixation Measuresmentioning
confidence: 99%
“…In other words, if flow direction is horizontal to surface, erosion will reduce. Zang et al ( 2016) showed that an anionic waterborne polyurethane could treat sand with zero compressive strength to achieve compressive strength larger than 1.5 MPa in a concentration lower than 10%w. It has been proven that the effect of higher polymer concentration on compressive strength (Iyengar et al 2012;Naeini and Ghorbanalizadeh 2010;Failed 2010b) and shear strength (Liu et al 2011;Naeini and Mahdavi 2009) appears at higher curing time (> 2 days).…”
Section: Polymersmentioning
confidence: 99%
“…From the measured shear wave velocity, Gmax was calculated by equation (2). Figure 4 shows the comparison of Gmax of treated and untreated sand at three different initial relative densities.…”
Section: Maximum Shear Modulus Gmaxmentioning
confidence: 99%
“…In geotechnical engineering, polymers have been used as the nontraditional additives for the artificial stabilizations of soft ground, sand fixing effect, polymer grouting, and to compose artificial floor surfaces. Recent studies on the use of polymers in engineering area focused on reducing toxicity of conventional polymers, developing novel polymers by industrial wastes [2] and applying polyurethane resin to reduce seismic damage [3]. Likewise, interest in the use of polymers in geotechnical engineering have been increased recently; however, there is the lack of understanding in the role of polymers on the behaviour of soils.…”
Section: Introductionmentioning
confidence: 99%